Resource use efficiency of banana production and impact of insurance scheme adoption on banana farming in Chitwan, Nepal - Dulal, Sunil; Kattel, Rishi Ram (International Journal of Applied Sciences and Biotechnology, 2020)
Eastern Chitwan of Nepal is the major banana producing hub. Farmers were categorized as small, medium and large banana producers on the basis of their banana cultivated land. Majority of the large famers had purchased banana insurance scheme. Altogether 150 sample households were selected on the basis of purposive simple random sampling to assess the resource use efficiency of banana farming and impact of insurance adoption in eastern Chitwan of Nepal in 2017. The primary data were collected by household survey using pre-tested semi-structured questionnaire, key informant interview and focus group discussion. The field survey showed that 50.58 percent respondents were male with average family size was 6.04. Only 10 percent of the sampled households were headed by female. Around 36 percent farm households had insured their banana. The B:C ratio of banana farming was 2.18. The research revealed that the farmers had an experience decreasing return to scale in banana production. Land preparation, suckers, labor and chemical fertilizer were the main factors that positively determined whereas the manure, irrigation, pesticide, and micronutrient had have negatively affected on banana production. Adoption of insurance scheme on banana farming had have positive effect on production of banana. It was estimated that the gross return will be increased by 0.012 percent in a farmer who had done insurance. The sampled farm failed to show their efficiency in using resources in banana production. There was further opportunity to increase banana production using more land preparation, suckers, chemical fertilizers and labor. Int. J. Appl. Sci. Biotechnol. Vol 8(2): 170-178